Handbook of Personal and Organizational Transformation (Springer International Publishing, 2018)
This handbook is based on the premise that there can be no organizational transformation without personal transformation. Anything else is just moving the chairs around on the deck of the Titanic, and we see that all too often in organizations today. Einstein said that we cannot solve problems from the same mindset that created the problems. In order to see positive change occur in the world, we must shift our consciousness to a high level of thinking and being, but we must also have systems or approaches that scale up, so that there is a collective shift in consciousness in groups, work teams, villages, governments, and corporations. This handbook aims to draw the best and most creative thinking about the field of transformation in one place, to present a comprehensive overview of leading edge transformation theories and approaches for both the academic and the practitioner. In fact, the lines between academic and practitioner are becoming more and more blurred these days. Many management faculty also consult to organizations, a practice that deeply enriches their teaching and research. And many successful full-time consultants conduct high quality research to support their approaches and change initiatives. This Handbook aims to be a creative dialogue in this space that integrates transformation theory and practice. The Handbook of Personal and Organizational Transformation acknowledges the classic literature and principles that have informed the field to date, but primarily showcases authors who are on the cutting edge of new theories and new approaches to give us their latest thinking. Some of these ideas are conjecture about what is possible in human and organizational development. Some of these approaches are currently being tested in the field and may not yet have scientific results. And some of these theories and models have stunning results, but may not have been published in academic journals because the author is a practitioner instead of an academic, or because the concepts are a little too far out of the mainstream. The aim of this book is to expand the reader's thinking and to encourage readers to be courageous about their involvement in creating transformation, at whatever level they feel called to do so. It will serve as an essential resource for researchers and students of organizational culture, leadership, and change management, as well as consultants, business and team leaders, and anyone interested in global trends and their impact on corporate culture. .